2014
DOI: 10.4028/www.scientific.net/kem.622-623.731
|View full text |Cite
|
Sign up to set email alerts
|

Production of Special Tubes with a Variety Cross-Sectional Shapes by Bunch Drawing and Fluid-Mandrel Drawing

Abstract: Recently, special tubes for high efficiency heat exchangers, high functionality electrodes, and super-micro medical needles have attracted attention. In order to produce such special tubes, however, a special processing method or tool is required. In this study, fabrication of special tube by bunch drawing and fluid-mandrel drawing were attempted. And it was revealed that the fabrication of special tubes with a variety of cross-sectional shape is possible, when a bunch of tubes, or a tube of large diameter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Recent developments in the fabrication of micro-tubes aim in particular to provide improved semi-finished products, with more economic manufacturing processes, for use in microsystem-based applications of medical engineering and microfluidics for heat exchangers. When primarily considering the fabrication of seamless metallic tubes, the investigated technologies can be divided into (a) dieless drawing techniques [5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], (b) process chains, applying scaled-down and partly modified tube drawing [36][37][38][39][40][41][42][43][44][45][46][47], and (c) manufacturing techniques of grooved micro-tubes for applications in heat exchange [43,[48][49][50][51][52][53][54]. Apart from this research into tube manufacturing processes, notable progress was also achieved in the design of the process and tools for the profile extrusion of tubular micro-profiles with a number of channels [55][56][57][58][59].…”
Section: Micro-tube Fabricationmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent developments in the fabrication of micro-tubes aim in particular to provide improved semi-finished products, with more economic manufacturing processes, for use in microsystem-based applications of medical engineering and microfluidics for heat exchangers. When primarily considering the fabrication of seamless metallic tubes, the investigated technologies can be divided into (a) dieless drawing techniques [5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], (b) process chains, applying scaled-down and partly modified tube drawing [36][37][38][39][40][41][42][43][44][45][46][47], and (c) manufacturing techniques of grooved micro-tubes for applications in heat exchange [43,[48][49][50][51][52][53][54]. Apart from this research into tube manufacturing processes, notable progress was also achieved in the design of the process and tools for the profile extrusion of tubular micro-profiles with a number of channels [55][56][57][58][59].…”
Section: Micro-tube Fabricationmentioning
confidence: 99%
“…A possible way of avoiding complications in removing a rigid mandrel from the drawn micro-tube consists in the use of liquids, such as water or oil, within the sealed tube during the drawing process, instead of the mandrel [45]. For the fabrication of micro-tubes made from stainless steel, with d o = 2.0 mm, by performing 21 passes, without intermediate annealing, the application of this fluid-mandrel drawing technique resulted in an increase of the wall thickness that was about 42% lower compared to that of the use of sinking [43], as shown in Figure 5.…”
Section: Scaled-down Tube Drawing and Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of numerical FE-based analysis showed that the drawing force can be reduced and that the drawing force is nearly independent of the length of the The work of frictional forces on the above-mentioned surfaces is completely transformed into heat, resulting in a local increase in the temperature of the drawing die, tube, and floating plug, as well as the lubricating film on the outer and inner surfaces of the tube [6,7]. The intensity of the heat released is a function of the following factors [8,9]:…”
Section: Introductionmentioning
confidence: 99%